1992
DOI: 10.1099/00221287-138-2-383
|View full text |Cite
|
Sign up to set email alerts
|

The glnA gene of the extremely thermophilic eubacterium Thermotoga maritima: cloning, primary structure, and expression in Escherichia coli

Abstract: The structural gene (glnA) encoding the glutamine synthetase (GS) of the extremely thermophilic eubacterium Thermotoga maritima has been cloned on a 6.0 kb Hind111 DNA fragment. Sequencing of the region containing the glnA gene (1444 bp) showed an ORF encoding a polypeptide (439 residues) with an estimated mass of 50088 Da, which shared significant homology with the GSI sequences of other Bacteria (Escherichia coli, Bacillus subtilis) and Archaea (Pyrococcus woesei, Sulfolbus solfataricus). The T. maritima gln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…However, certain distinctive sequence signatures (Fig. 2) the GSI species examined (48,51,63), strongly support the root placement inferred from both DNA sequence-distance (Fig. 3A) and maximum-likelihood (Fig.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, certain distinctive sequence signatures (Fig. 2) the GSI species examined (48,51,63), strongly support the root placement inferred from both DNA sequence-distance (Fig. 3A) and maximum-likelihood (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…2), one group comprising all three archaea, Thermotoga species, and the low-G+C gram-positive bacteria, and the other encompassing S. coelicolor, cyanobacteria, and proteobacteria. Notably, these signatures also separate the GSIs whose activity is modulated by reversible adenylylation of the subunits (cyanobacteria, proteobacteria, S. coelicolor) from those whose subunits are not adenylylated (21,48,51,63).…”
Section: Asp Pgslelalealendhafltdtgvftedfiqnwidyklanevkqm-----------mentioning
confidence: 99%
“…Accordingly, these hyperthermophiles contain biomolecules that are adapted to these elevated temperatures, both in structure and function. Cloning and expression of genes from thermophiles into mesophilic hosts demonstrated that this enhanced-stability is mainly an intrinsic feature of the enzymes (Zwickl et al, 1990;Moracci et al, 1992;Sanangelantino et al, 1992). Cloning and expression of genes from thermophiles into mesophilic hosts demonstrated that this enhanced-stability is mainly an intrinsic feature of the enzymes (Zwickl et al, 1990;Moracci et al, 1992;Sanangelantino et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Oligonucleotides were synthesized with a 380A DNA synthesizer (Applied Biosystems). Specific sequencing of the LDH gene in pTLDH25 was started with a degenerated oligonucleotide corresponding to the aminoterminal sequence and the codon usage of known Thermotoga genes (Bachleitner et a1.,1989;Sanangelantoni et al, 1992;Tomschy et al, 1993). The start primer was 5'AT-GAAGGGXTTTGCXAGGGAGATGGT 3' (X = G or T).…”
Section: Dna Sequencingmentioning
confidence: 99%